2023
DOI: 10.1186/s12902-023-01296-4
|View full text |Cite
|
Sign up to set email alerts
|

Central diabetes insipidus: a late sequela of BNT162b2 SARS-CoV-2 mRNA vaccine?

Abstract: Background The development of an effective vaccine is a powerful tool to contain the global spread of coronavirus disease 2019 (COVID-19). Still, it raises potential safety concerns about the subsequent enhancement of associated immunopathology. Increasing evidence shows that the endocrine system, including the hypophysis, may be involved in COVID-19. Moreover, occasional but increasing reports of endocrine disorders involving the thyroid have been reported after the severe acute respiratory sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…There is no description of the recovery of hormone levels in the three previous cases of hypopituitarism induced by COVID-19 vaccines [ 11 13 ]. In some cases of AVP deficiency, long-term replacement of vasopressin is necessary [ 6 8 , 11 ]. Nevertheless, it is also reported that in about half cases of thyroid disorder, at least partial recovery was observed within 5 months [ 11 ], indicating a relatively better prognosis in ASIA than other etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…There is no description of the recovery of hormone levels in the three previous cases of hypopituitarism induced by COVID-19 vaccines [ 11 13 ]. In some cases of AVP deficiency, long-term replacement of vasopressin is necessary [ 6 8 , 11 ]. Nevertheless, it is also reported that in about half cases of thyroid disorder, at least partial recovery was observed within 5 months [ 11 ], indicating a relatively better prognosis in ASIA than other etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…However, CDI from Pfizer vaccine may take 8 weeks to develop. 81 Improvement in pituitary function follows hormonal replacement.…”
Section: Hypophysitismentioning
confidence: 99%
“…Most of these patients had no previous known pituitary disease or SARS-CoV-2 infection. The median time between vaccination and the onset of pituitary disorder was 3 days and ranged from one [85][86][87][88] to sixty days [89]. Description of the reported cases are summarized in supplementary Table 1.…”
Section: Pituitary Gland and Sars-cov-2 Vaccinementioning
confidence: 99%
“…Concerning hypophysitis, this is a sporadic disease with an incidence of ~1 in 9 million/year in the form of primary hypophysitis [96]. Hypophysitis following SARS-CoV-2 vaccine present most often as isolated arginine vasopressin (AVP) deficiency (central diabetes insipidus) due to infundibuloneurohypophysitis [89,[97][98][99]. AVP deficiency was also reported with subsequent development of optic neuritis [100].…”
Section: Pituitary Gland and Sars-cov-2 Vaccinementioning
confidence: 99%
See 1 more Smart Citation